2010
DOI: 10.2527/jas.2009-1874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine respiratory disease and overall pathogenic disease incidence on carcass traits1,2

Abstract: The objective this study was to evaluate the effects of incidence of bovine respiratory disease (BRD) and overall incidence of pathogenic diseases (IPD) on carcass traits. Two independent populations were used. The first population included crossbred steers (GPE7; n = 642) derived from sires of 7 Bos taurus breeds: Angus, Charolais, Gelbvieh, Hereford, Limousin, Red Angus, and Simmental. The second population included crossbred steers (GPE8; n = 621) derived from tropically adapted Bos taurus breeds and Bos in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
3
19
1
Order By: Relevance
“…In the present study, the carcasses of treated steers had lower fat content than the carcasses of healthy steers, which corroborates the findings of Garcia et al (), Gardner et al (), Montgomery et al () and Snowder et al (). Gardner et al (), who analyzed Charolais steers, and Montgomery et al (), who investigated heifers, found that animals treated for pneumonia at least once during rearing and fattening were characterized by lower fat deposition than healthy animals.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the carcasses of treated steers had lower fat content than the carcasses of healthy steers, which corroborates the findings of Garcia et al (), Gardner et al (), Montgomery et al () and Snowder et al (). Gardner et al (), who analyzed Charolais steers, and Montgomery et al (), who investigated heifers, found that animals treated for pneumonia at least once during rearing and fattening were characterized by lower fat deposition than healthy animals.…”
Section: Discussionsupporting
confidence: 93%
“…As in most epidemiological studies on BRD, producer based diagnosis was used, because this approach is closest to realistic on farm procedures and therefore better interpretable by the industry itself [3,4,9,10,33-35]. For diarrhea, arthritis and otitis, straightforward case definitions based on obvious symptoms were provided to the producers, and reporting bias is believed to be limited for these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic BRD also had a significant negative effect on carcass quality and fat cover, as documented for feedlots [6,9]. In feedlots chronic unresponsive pneumonia has been associated with Mycoplasma bovis and bovine viral diarrhea virus [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for the different association observed for ADG between that study 4 and the present study is unknown; however, differences in management, having a bull-only population, or other unreported study characteristics are likely. Another study 12 found changes in production traits associated with treatment for any preweaning disease, including bovine respiratory disease, IBK, and infectious pododermatitis; however, the sole contribution of IBK to losses was not determined. Other studies [13][14][15] that evaluated disease occurrence and production traits have focused on postweaning disease, in particular, bovine respiratory disease.…”
Section: Discussionmentioning
confidence: 99%